Link Budget Planning and Modulation Performance Evaluation of a 1550 nm Terrestrial FSO Network for Intra-Office Scenarios - Fitri Elvira Ananda; Zulhelman Zulhelman; Mohamad Fathurahman (Universitas Bandar Lampung (UBL), 2026)
This study presents a link budget planning analysis and performance evaluation of a free-space optical (FSO) communication system for short distances in an intra-office scenario. A geometry-based link budget analysis is applied to model key parameters, including beam divergence, receiver aperture, and link margin over distances ranging from 10 to 500 meters. The link budget analysis is conducted under clear-sky conditions to establish a baseline performance for the proposed intra-office FSO deployment. Furthermore, the bit error rate (BER) performance is evaluated across different signal-to-noise ratio (SNR) levels for OOK, BPSK, and QPSK modulation formats. The modulation schemes are compared based on the required SNR to achieve a target BER, the corresponding received optical power, and the maximum achievable transmission distance under identical system parameters. The results confirm the feasibility of achieving data rates up to 1 Gbps for intra-office FSO links and demonstrate that higher-order modulation schemes, particularly QPSK, provide longer transmission distances and improved power efficiency compared with OOK.